2010
DOI: 10.1002/pd.2433
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma soluble fms‐like tyrosine kinase‐1 and free vascular endothelial growth factor at 11 to 13 weeks of gestation in preeclampsia

Abstract: Evaporation‐induced intercalation of nanosheets of organosilica, organoclay or various organic polymers within the interlayer spaces of an oriented bacteriorhodopsin/lipid membrane mesolamellar film is used to prepare stable, self‐supporting biofunctional hybrid nanocomposites with photochromic and photoelectric properties. Compared with unmodified purple membrane films, mesolamellar nanocomposites containing intercalated organosilica exhibit enhanced stability in their photoelectric response at high relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 51 publications
8
51
0
1
Order By: Relevance
“…Concerning sFlt-1, although second- and third-trimester levels before the onset of PE have been consistently reported to be higher [11,16,21], findings in first-trimester patients are conflicting. Several studies reported similar sFlt-1 values between cases and controls, either when overall PE was used as main outcome measure [16,22,23,24,25,26] or when patients were grouped as early- and late-onset disease [27]. Two studies including only late-onset PE reported higher first-trimester levels of sFlt-1 [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning sFlt-1, although second- and third-trimester levels before the onset of PE have been consistently reported to be higher [11,16,21], findings in first-trimester patients are conflicting. Several studies reported similar sFlt-1 values between cases and controls, either when overall PE was used as main outcome measure [16,22,23,24,25,26] or when patients were grouped as early- and late-onset disease [27]. Two studies including only late-onset PE reported higher first-trimester levels of sFlt-1 [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, four studies reported decreased levels [19,30,31,32], of which all but one [32] included early- and late-onset cases. On comparing published studies on sFlt-1, it is remarkable that levels among controls varied widely, from 166 pg/ml [30] to 6,349 pg/ml [27]. The variability among studies might be explained by differences in the GA at sampling, ranging from 8 to 14 weeks of gestation, use of serum or plasma, type of commercial kits used, and storage conditions of samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…102 Finally, in most studies PlGF is a more sensitive and precise predictor of preeclampsia and FGR than any other single biomarker. [103][104][105][106] Biomarkers that are predominantly maternal in origin (such as inflammatory cytokines or angiotensin II Type I receptor-autoantibodies; see Other Potential Biomarkers for Redefinition of Preeclampsia) would be expected to reflect maternal not placental pathophysiology of preeclampsia and for this reason are not the focus of this review.…”
Section: Redefining Preeclampsia Using Circulating Trophoblast-derivementioning
confidence: 99%
“…Some studies have found that low PlGF is a good predictive factor in first trimester for preeclampsia [39][40][41][42][43], while other studies showed no predictive value for PlGF in first trimester [44][45][46][47]. Most studies have found that low PlGF in the second trimester predicts later occurrence of preeclampsia [47][48][49][50][51][52][53][54]. The ratio of the PlGF/sFlt-1 is well described and this new value has shown as an appropriate biochemical marker for prediction of PE [55].…”
Section: Placental Growth Factormentioning
confidence: 99%